The Influence of Learning Motivation and Learning Understanding on Student’s Cumulative Grade Point Average - Napitupulu, Rizal Afif A.; Risia Yogasnumurti, Raras; Setiagraha, Dika (Universitas Negeri Medan, 2025)
Indonesia is still struggling to become a developed country. In the process, it is necessary to maximize various aspects, both natural resources and human resources (HR). The purpose of this study is to see whether learning motivation and understanding of learning affect the Student Achievement Index which will support their future career. Students that learning at university who will later have a career and become HR are expected to be able to make Indonesia a developed country driven by the economy. While studying at university, intention and motivation play an important role. Because when someone has strong motivation, he can achieve his targets and also have a good plan for his future career. Previous research has also proven that motivation is an important part of learning understanding. Motivation is also part of emotional intelligence (EQ), where emotional intelligence is also an important part of learning besides intellectual intelligence (IQ). The hypothesis of this study is that students who have good motivation tend to achieve good learning understanding and also get a good GPA and help plan their future careers. The sample of this study was students of the Sriwijaya State Polytechnic, Bukit class, Sriwijaya State Polytechnic, totaling 65 people. This research method uses regression. Student motivation, learning understanding and GPA were measured and collect by a questionnaire with a Lickert scale. Then, the data was analyzed using SPSS software. The result is that student motivation has a influence on student learning understanding and their GPA.